SISTEM INFORMASI PENERIMAAN PEGAWAI BARU BERBASIS WEBSITE PADA PT. JAMKRIDA KALIMANTAN TENGAH - Monica Cinthya; Licantik Licantik; Ariesta Lestari (Universitas Palangka Raya, 2020)
The process of employee’s recruitment at PT. Jamkrida still uses the manual methods in terms of registration, selection and announcement the result. These process is tme consuming and could be very expensive. Therefore a new system is needed to manage the recruitment process of new employees at PT. Jamkrida Kalimantan Tengah. Through this system the registration and selection process can be done well, precisely and quickly. Employee Recruitment System of PT. Jamkrida Kalimantan Tengah can be used as a solution in handling the process of hiring new employees in a company. The testing method performed on this website is a blackbox. From the tests conducted it can be concluded that the existence of a new web-based employee recruitment information system or e-recruitment company, is very helpful in the process of recruiting applicants, such as the committee can process applicant data quickly because applicant data will be accommodated in a database so that applicant data does not accumulate in file storage cabinets, as well as to process and search applicants' data can be done easily, with the online test system it can be easily and quickly to make corrections to answers because it is done by the system.